الحرية الاقتصادية والنمو في الاقتصاد الليبي - حسن الدامي بدر, (Scientific Journal of University of Benghazi, 2021)
In an effort to provide the appropriate environment for growth, many countries have tended during the past decades to adopt Policies expand the scope of economic freedom, With the emergence of indicators that measure the level of economic freedom for countries, the number of empirical studies that tried to explore and test the relationship of economic freedom with economic growth increased. The results of most of them confirmed that the countries that enjoy greater economic freedom, and which witness an improvement in their level, record faster and higher levels of economic growth. This study aims to explore and test this relationship in the Libyan economy during the period (1996-2012) in the short and long run. For this purpose, the study used, the tests and methods of the modern quantitative standard approach, as tests of unit root, Causality and co integration, the results showed that there is no relationship, either in the short or in the long run, between the index of economic freedom at its current level and the growth in the Libyan economy classified in terms of economic freedom within the category of repressed economies.